2007
DOI: 10.1063/1.2767241
|View full text |Cite
|
Sign up to set email alerts
|

Silicon nanocrystal-based photosensor on low-temperature polycrystalline-silicon panels

Abstract: Characteristics and stress-induced degradation of laser-activated low temperature polycrystalline silicon thin-film transistors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…5 These properties have made Si NCs useful in various devices, such as light-emitting devices, 6-8 solar cells, [9][10][11] and photodetectors. [12][13][14][15][16] Recently, the sizedependent properties of Si NCs were studied to realize silicon-based wavelength-sensitive photodetectors without using color filters, 12 because it has been shown that the absorption onset energy of silicon can be controlled by using quantum confinement effects in Si NCs. 2 Although a few reports have demonstrated photodetectors using Si NCs embedded in silicon oxide 13,14 and silicon nitride, 15 there has been no report on the relationship between the size of Si NCs and the photocurrent of Si NC photodetectors.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…5 These properties have made Si NCs useful in various devices, such as light-emitting devices, 6-8 solar cells, [9][10][11] and photodetectors. [12][13][14][15][16] Recently, the sizedependent properties of Si NCs were studied to realize silicon-based wavelength-sensitive photodetectors without using color filters, 12 because it has been shown that the absorption onset energy of silicon can be controlled by using quantum confinement effects in Si NCs. 2 Although a few reports have demonstrated photodetectors using Si NCs embedded in silicon oxide 13,14 and silicon nitride, 15 there has been no report on the relationship between the size of Si NCs and the photocurrent of Si NC photodetectors.…”
mentioning
confidence: 99%
“…Moreover, a clear relationship between the absorption in Si NCs and the photocurrent of Si NC photodetectors has never been reported because most studies 12,14-16 have been performed with diode or transistor structures, where the photocurrent is heavily affected by the current from silicon wafers. Furthermore, there is some disagreement over the origin of photoresponse, as a recent study 16 has shown, that the photocurrent of photodetectors with Si NCs embedded in silicon oxide is generated by the absorption of light in the interface states between Si NCs and silicon oxide.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the fitting procedure, we excluded the values of the two smallest quantum dots from a series of target values and set size-dependent weights for the fitting 5 , because any trials containing the values of the smallest quantum dots while giving same weights for all quantum dots in the fitting procedure have enlarged differences for the medium sized (2.2, 2.7, and 3.5 nm diameter) quantum dots. 5 We set the weights for fitting method as follows. In Si clusters, the weights are 0.1 for D = 1.5 nm, 0.4 for D = 2.2 nm, and 1.0 for the others.…”
Section: Order(n) Algorithm Based On the Krylov Subspace Methodsmentioning
confidence: 99%
“…Various kinds of nano-structured materials such as quantum dots, in which novel physical and chemical properties appear by the miniaturization of the bulk materials, have been studied to realize desirable and tunable properties suitable for various applications. Since Silicon is a resource in abundant supply with high safety to the environment and the human body, Si quantum dots particularly attract much attention as one of the promising candidates of materials for the applications to solar cell, alternatives to traditional organic dyes, photo-sensors, light-emitting diodes, single electron devices, bio-medical tags, and so on [1][2][3][4][5][6][7][8]. Although the investigations on C and SiC quantum dots [9][10][11], which consist or include another abundant resource in group IV element, C, are not as extensive as those on the Si quantum dots, an understanding of the behavior of energy gaps of these systems in wider ranges of temperature and size will open up newer avenues for applications.…”
Section: Introductionmentioning
confidence: 99%